Taxonomic databases for Bursaphelenchus and other aphelenchoid nematodes - Eisenback, Jonh (2012)
Nematodes are the most abundant metazoans, comprising more than 80% of all animals alive today. Since 1743, when Needham (Needham, 1743) described the first nematode, approximately 20,000 - 30,000 species have been named, with estimates of species remaining to be described ranging from 100,000 to 1 million (Blaxter, 2004; De Ley, 2000). Unfortunately, the taxonomic community is woefully inadequate for this task. The number of taxonomists currently describing new species of nematodes around the world is less than 100, and significant increases are not expected. If each of these taxonomists were able to describe 10 new species every year, it would take between 100 to 1,000 years to name these yet to be described species.